Implementation of QRIS Transactions in the Development of the Digital Economy in Medan City: Implementasi Transaksi QRIS Dalam Perkembangan Economi Digital di Kota Medan - Mardiah Gea, Ulfa (UPMI Proceeding Series, 2023)
In encouraging the improvement of the digital economy, it is necessary to utilize technology, one of which is by using non-cash transactions. Non-cash transactions currently circulating in the form of Quick Response Code Indonesian Standard (QRIS). With the presence of the QRIS system, it offers transactions that are faster and more convenient than cash. This study examines the Implementation of QRIS Transactions in the Development of Digital Economy in Medan City. this research uses a qualitative method with a descriptive approach. Data collection using secondary data. The results of the study indicate that the QRIS Implementation provides convenience for the community in carrying out non-cash transactions and the security of QRIS user data. as well as efforts to increase QRIS users with socialization, education, community literacy about using QRIS.